3D Dislocation structure evolution in strontium titanate: Spherical indentation experiments and MD simulations. Issue 3 (2nd November 2016) - Javaid, Farhan; Stukowski, Alexander; Durst, Karsten
Abstract: In the present work, the dislocation structure evolution around and underneath the spherical indentations in (001) oriented single crystalline strontium titanate (STO) was revealed by using an etch‐pit technique and molecular dynamics (MD) simulations. The 3D defect structure at various length scales and subsurface depths was resolved with the help of a sequential polishing, etching, and imaging technique. This analysis, combined with load‐displacement data, shows that the incipient plasticity (manifested as sudden indenter displacement bursts) is strongly influenced by preexisting dislocations. In the early stage of plastic deformation, the dislocation pile‐ups are all aligned in 〈100〉 directions, lying on {110}45 planes, inclined at 45° to the (001) surface. At higher mean contact pressure and larger indentation depth, however, dislocation pile‐ups along 〈110〉 directions appear, lying on {110}90 planes, perpendicular to the (100) surface. MD simulations confirm the glide plane nature and provide further insights into the dislocation formation mechanisms by tracing the evolution of the complete dislocation line network as function of indentation depth.